A Flor de Piel Exploring Latin American Decolonial Aesthetics forReligious Studies: Sensing Puerto Rican Media - González-Justiniano, Yara (Journal for Religion, Film and Media)
A current opening for research in the field of religion, film, and media is the interpretation of cultural production through the sensing and knowing that stems from decolonial approaches. In this article, I argue for the use of a Latin American decolonial aesthetics in this field of study, specifically in exploring examples from Puerto Rican art and media that incite community-making practices in association with a religious/ theological imagination. I provide a list of eight key characteristics of decolonial aesthetics and introduce the expression a flor de piel (brought to, or sensed on, the surface) to describe the type of sensing that these works of art produce in an embodied dialectics between the medium and its audience.